Composite proton conducting membranes from chitosan, poly(vinyl alcohol) and sulfonic acid-functionalized silica nanoparticles. (6th January 2021) - Kamjornsupamitr, Trin; Sangthumchai, Thanakorn; Saejueng, Pranorm; Sumranjit, Jitapa; Hunt, Andrew J.; Budsombat, Surangkhana
Abstract: Composite proton conducting membranes were successfully synthesized from chitosan, poly (vinyl alcohol) and sulfonic acid-functionalized silica nanoparticles. Sulfosuccinic acid (SSA) and glutaraldehyde were used as double crosslinking agents, where the effect of SSA content on membrane properties, including water vapor absorption, water uptake, ion exchange capacity, and proton conductivity was investigated and were found to increase as a function of SSA loading. The most promising membrane was then formed into a composite with either silica nanoparticles containing poly (2-acrylamido-2-methyl-1-propanesulfonic acid) (PAMPS-Si) or poly (styrene sulfonic acid) (PSSA-Si). PAMPS-Si and PSSA-Si were characterized by thermogravimetric analysis (TGA), transmission electron microscopy (TEM), and Fourier transform infrared spectroscopy (FTIR). The effects of nanoparticle loading and polymer shell on membrane properties were studied. Proton conductivity increased at higher nanoparticle loadings, and reached a maximum of 3.8–3.9 × 10 −3 S/cm at 20% loading. The influence of polymer shell on membrane properties was not significantly observed. Graphical abstract: Image 1 Highlights: Composites of IPNs of chitosan and PVA, and sulfonic-acid Si particles were prepared. Effects of sulfosuccinic acid, Si particle loading, and polymer shell were studied. Proton conductivity increased with increasing Si particle loading. Composite membranes showed good hydrolytic, thermal and oxidative stabilities.